Willingness of the United States general public to participate in kidney paired donation - Segev, Dorry L. (2012)
BACKGROUND: Availability of kidney paired donation (KPD) is increasing in the United States, and a national system through UNOS is forthcoming. However, little is known about attitudes toward KPD among the general public, from which donors (particularly non-directed) are drawn. METHODS: In a national study, we assessed the public's attitudes regarding participation in KPD. RESULTS: Among 845 randomly selected participants, 85.2% of respondents were either “extremely willing” or “very willing” to participate in KPD. Experiences with the medical or organ transplant systems, such as undergoing surgery, having a primary medical provider, a living will, a friend who donated or received an organ, and considering donation after death, were associated with increased willingness. However, increased age, male sex, African American race, Hispanic ethnicity, distrust of the medical system, and not understanding organ allocation were associated with less willingness. CONCLUSIONS: We identify strong support for KPD but some important potential barriers to participation which should be considered as KPD programs are implemented.